Georgia Warr's journey toward aromantic asexual identity in Alice Oseman's Loveless - Archylia Putri Harahap; Anik Cahyaning Rahayu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines Georgia Warr's journey toward understanding and accepting her aromantic asexual identity in Alice Oseman's Loveless. The research aims to analyze the stages of Georgia's identity formation and to reveal how heteronormative expectations influence her experiences throughout the process of self-discovery. This study employs a qualitative descriptive method using a literary psychological approach combined with queer theory. The primary data are collected from the novel Loveless, while secondary data are obtained from books, scholarly journals, and previous studies related to asexuality, aromanticism, identity development, and heteronormativity. The data are analyzed through close reading, data classification, interpretation, and contextual analysis. The findings demonstrate that Georgia's identity development occurs through several interconnected stages: identity confusion, self-questioning, denial, realization, coming out, and self-acceptance. Throughout these stages, Georgia struggles with social expectations that equate happiness with romantic and sexual relationships. Her interactions with members of the LGBTQIA+ community gradually help her understand that romantic and sexual attraction are not universal experiences. Ultimately, Georgia recognizes that her identity as an aromantic asexual individual is valid and does not diminish her ability to build meaningful relationships. This study contributes to literary criticism by highlighting the importance of aromantic and asexual representation in contemporary young adult fiction and demonstrating how literature challenges dominant heteronormative assumptions regarding love, intimacy, and personal fulfillment.